Ruang Publik Digital dalam Diskusi Agama dan Kepercayaan: Analisis Konten Siniar “Berbeda Tapi Bersama” Episode Ke 20 Inti Ajaran Aliran Kebatinan Perjalanan - Nuha Fidaraini (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2022)
Aliran Kebatinan Perjalanan is one of the minority beliefs in Indonesia. The two figures from that belief were invited as guest stars in the 20th episode of the podcast Berbeda Tapi Bersama. Through the podcast, the two figures voiced their views and experiences as a minority group in a country that actually already has rules for its citizens to be free to choose the religion and belief they believe in. Based on the three dimensions of Dahlgren's online public sphere, structural, representational and interactional, the 20th episode of Berbeda Tapi Bersama reveals that the podcast has the capability to manifest a communicative public sphere by combining the structure of digital and traditional public sphere, the participants have several different views so it makes the discussion to be the representation of diversity and the interaction of the participants produced exchange of views and common goals. Overall, through those findings, podcast is one of the digital media that can be expected to be used more as part of the digital public sphere.